The geodiversity valuation system with focus on ecosystem services sensu Murray Gray - da Silva, Matheus Lisboa Nobre; Nascimento, Marcos Antonio Leite do (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Geodiversity is the variety of abiotic elements present in nature, including its assembly and processes. All natural diversity needs to be preserved and have its consumption made sustainable, as is already accepted for biodiversity. It’s possible to identify values of geodiversity that can support the conservation of abiotic resources process. The system here presented was introduced by the geographer Murray Gray, through the conception one intrinsic value, five services (regulation, support, provision, cultural, and knowledge) and 25 goods and processes. This new model sensu Murray Gray, based on the abiotic ecosystem definition, is presented as an example of a qualitative evaluation system of geodiversity that can be applied to studies in Brazil. It’s exemplified here the application of this system on the identification of geodiversity in Natal, Rio Grande do Norte , northeastern Brazil, geologically formed by cenozoic covertures, but with a wide range of abiotic diversity on its landscapes and in the use of stone in historical monuments and buildings. Therefore, it is proposed here to update the evaluation system of abiotic diversity in the country, in order to promote greater dialogue between the studies of the natural diversity of the planet.
Keywords: Geodiversity; Valuation; Services; Ecosystem